THE EFFECT OF ROLE CONFLICT, ROLE AMBIGUITY, AND SELF EFFICACY ON AUDITOR PERFORMANCE - Evania Sesa, Patricia Gloria (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study aims to test and empirically prove the influence of role conflict, role ambiguity, and self-efficacy on auditor performance. The research sample was 101 auditors from public accounting firms in Jakarta. The analytical method in this study uses multiple linear regression analysis. The results showed that (1) role conflict had a positive affected auditor performance (2) role ambiguity had a positive effect on auditor performance (3) self-efficacy had a positive effect on auditor performance.